A leitura da atual crise capitalista na obra de Michael Roberts: aportes e limitações - Silva, Luís Eduardo Pereira da (2024)
This master thesis addresses the work of the English Marxist economist Michael Roberts, aiming to understand how, based on this author's theoretical production, it is possible to explain contemporary capitalism and its crisis – or, in his terms, the “Long Depression”. Apart from a critical exposition of Robert’s research, including its theoretical foundation, methodological apparatus and conclusions, the goal is to position the author within the broader field of Economics – in contrast to other traditions – and within the theoretical field of Marxism, thus highlighting the contributions and possible shortcomings or existing flaws. In this way, the research has a dual objective: to present and systematically analyze the author's theoretical work to Brazilian readers, and to critically examine, based on it, a comprehensive overview of the crisis of contemporary capitalism. Apart from an introduction, this thesis includes four chapters. Chapter 2 aims to present the three laws of motion of capitalism as developed by Roberts, with Marx's work serving as a key reference. The third chapter explores the methodological tools employed by Roberts to learn about the dynamics of the economy, namely: measuring the rate of profit, the global profit rate and the cycles of the capitalist economy. The fourth chapter, the most relevant to the aim of this work, deals with Robert’s explanation of the Great Recession and his thesis about current capitalism – asserting that it is experiencing a “Long Depression”. Finally, the fifth chapter, the conclusion, is titled “Final Considerations: the agony of the Long Depression – persistence and validity of a thesis”. It revisits the main themes from the preceding chapters, incorporating the perspectives of the author's critics and my own assessment of the strengths and shortcomings of his work.